La calidad de agua para consumo humano y su incidencia en el bienestar familiar y comunitario y el rol del trabajador social en la parroquia Zurmi, canton Nangaritza, provincia de Zamora Chinchipe - Villa Illescas, Tania Susana (2015)
The present study about "THE QUALITY OF it DILUTES FOR HUMAN CONSUMPTION AND THEIR INCIDENCE IN THE FAMILY AND COMMUNITY WELL-BEING AND THE SOCIAL WORKER'S LIST IN THE PARISH ZURMI, CANTON NANGARITZA, COUNTY DE ZAMORA CHINCHIPE." he/she is carried out it in the execution of the general outlined objective, it is framed in the determination of the "grade of incidence of the quality of the water for human consumption and working of the Worker Social" investigation that I carry out it taking like conceptual base that the water is the indispensable element for the human being's life and the normal development of its productive and reproductive activities, being indispensable to prepare this element in the quantity and enough quality that allow to the families the daily development; however, the reality of the investigated neighborhood is devastating, they don't have information clarified about the quality of the water that you/they consume, being generated a great quantity of people with physical and biological alterations that go to the position of health of the town, presented parasitosis squares, diarrheas, mushrooms in skin and hairy leather, without having statistical accessible or studies from the social point of view of the impact that causes it in the families and the community. The investigation was based on the scientific method, supported in the chemical bacteriological analysis, he/she interviews, it interviews and registrations of parts doctors as sources of gathering of information. The population is aware of the necessity of carrying out actions that bear to the solution of this problem to be able to have a water of quality that impedes the proliferation of illnesses, in a same way the necessity you/he/she exists of having the intervention of a professional in Social Work, since historically you/he/she has been located in the solution of economic problems partner for the attainment of the health, education and other intervention areas that justify her participation so much in the formulation, planning, execution and evaluation of the politicians of health properly interrelated with the environment, also completing integration functions, education and coordination. In a general vision it is deduced that the quality of the water that you/they consume doesn't lend the total guarantees for its consumption and that it is very necessary to adopt sanitary measures to prevent illnesses of origin hídrico in this sector, in front of this discovery from the perspective of the Social Work thinks about a project of prevention to face this problem with the active participation of the residents. It is commendable to ponder the population's approaches intervened as for defining properly identified strategies with the Social Worker's protagonistic list, to consider pertinent as for motivation, coordination so much with the families, population in general and local authorities, emprendimientos and/or processes of mutual help to the deprived families of resources.